Behavioral financial engineering in the fixed-income market: The influence of the coupon structure - Mathias Eickholt (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2014)
In this paper we investigate the influence of coupon structure on the financial behavior of Individual Investors in the fixed-income market. Examining circa 26 million decisions on 204 standard putable bonds with different coupon offerings our major findings are: (i) Products with a flat coupon structure and a high duration attract fewer investors and are significantly more often exercised early, whereas financially equal products with a steeply rising coupon structure arouse more interest among investors and are less often redeemed early. (ii) The shape of the upcoming coupon structure is an important basis on which investors decide which putable bond in a portfolio to exercise early. (iii) Issuers who exploit empirical patterns related to a bonds coupon structure through "behavioral financial engineering" can benefit from a lower liquidity demand and a diminishing empirical option value.
Keywords: G02; G11; 650; individual investors; product design; putable bond